Investigating Mechanical and Physical Properties of Stir Casted Al6061/Nano Al2O3/Quartz Hybrid Composite - Dagim Tirfe; Abraham Woldeyohannes; Bonsa Hunde; Temesgen Batu; Eaba Geleta (Advances in Mechanical and Materials Engineering)
Aluminum alloys are widely used in different engineering application areas, such as aerospace, automotive, and marine industries. However, their properties need some improvement in order to enlarge their application area. Thus, the objective of the study was to improve the physical and mechanical properties of Al6061 aluminum alloy by reinforcing it with nano-Al2O3 and micro-quartz particles. The investigation primarily was focused on studying the impact of quartz particles on the mechanical and physical properties of an Al6061/nano Al2O3/quartz hybrid composite. The hybrid composite was developed using a stir casting technique, by varying the weight percentage of quartz particles at 3%, 6%, and 9%, while maintaining a constant weight percentage of nano-Al2O3 at 3.5%. To evaluate the composite's properties, test samples were prepared according to ASTM E9-09 and ASTM E23 standards for hardness, compressive strength, creep, and impact energy absorption, respectively. The results of the investigation demonstrate that, with the addition of 9 wt.% of micro-quartz particles and 3.5 wt.% of nano-Al2O3 nanoparticles, all mechanical and physical properties of the matrix were improved, except for the impact strength. Based on these results, the developed hybrid composite material can be recommended for light weight automotive spare parts such as brakes and clutch discs.